2021
DOI: 10.1038/s41598-021-87619-8
|View full text |Cite
|
Sign up to set email alerts
|

Facile isolation and analysis of sporopollenin exine from bee pollen

Abstract: We present facile methods to obtain purified sporopollenin exine capsules, and provide mass balances for classical and novel purification procedures. An ionic liquid, tetrabutyl phosphonium hydroxide turned out to be the most effective in removing the intine wall. The sporopollenin capsules were investigated by fluorescent microscopy, AFM, solid-state NMR and infrared Raman spectroscopy. The latter two methods showed that sunflower and rape exines have different proportions of O-aliphatic and aromatic constitu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 63 publications
(58 reference statements)
0
3
0
Order By: Relevance
“…Hegedu ¨s et al studied the chemical structure of sporopollenin from sunflower and oilseed rape by solid-state NMR spectroscopy, whose results were similar to that of pine sporopollenin. 42 Through heteronuclear single quantum coherence (HSQC) NMR spectroscopy, Xue et al further revealed that, in addition to aliphatic compounds, sporopollenin from lily also contains phenolic compounds and phenylpropane derivatives, including lignin guaiac G units, paracoumarate (p-CA), paraben (p-BA) and ferulate (FA) (Fig. 2d).…”
Section: Yuetong Wangmentioning
confidence: 99%
See 1 more Smart Citation
“…Hegedu ¨s et al studied the chemical structure of sporopollenin from sunflower and oilseed rape by solid-state NMR spectroscopy, whose results were similar to that of pine sporopollenin. 42 Through heteronuclear single quantum coherence (HSQC) NMR spectroscopy, Xue et al further revealed that, in addition to aliphatic compounds, sporopollenin from lily also contains phenolic compounds and phenylpropane derivatives, including lignin guaiac G units, paracoumarate (p-CA), paraben (p-BA) and ferulate (FA) (Fig. 2d).…”
Section: Yuetong Wangmentioning
confidence: 99%
“…5d). 42 4.1.2 Enzyme extraction. Because the exine of multicellular pollen is thin and easy to break, the enzymatic method based on the digestion of enzymes is well suited.…”
Section: Extracting Sporopollenin Exine Shellsmentioning
confidence: 99%
“…It is obtained as a result of lactic acid fermentation of pollens by some bacteria and fungi (4)(5)(6). In addition, corbiculate bees add regurgitated fluid with the grains to facilitate pollen adherence to the OPEN ACCESS EDITED BY pollen baskets and pollen grains (8)(9)(10). BP is collected by adult forager bees and transported to the hive.…”
Section: Introductionmentioning
confidence: 99%